1993
DOI: 10.1115/1.2919269
|View full text |Cite
|
Sign up to set email alerts
|

A Multiobjective Optimization Strategy with Priority Ranking of the Design Objectives

Abstract: Generally, two types of priorities are considered among multiple objectives in the design of machine structures. One of these objectives is named the “hard objective” and is the absolutely indispensable design requirement while the other is called “soft objective” and has a lower priority order. This paper proposes a multiobjective structural optimization strategy with priority ranking of the design objectives. Further, this strategy is demonstrated on the actual example of a motorcycle frame structural design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…It is applied to a bridge structure of pre-stressed concrete. A classical optimization strategy proposed by Matsumoto et al [110], which considers a priority among the objectives to be minimized, is applied to the structural design of motorcycles considering the torsional rigidity maximization, the reduction of the level of dynamic response, and the minimization of the weight of this structure. The proposed method is based on the lexicographic approach, and the optimization is performed successively from the superposition of single-objective optimizations (multiobjective fronts are not achieved).…”
Section: Classic Optimizationmentioning
confidence: 99%
“…It is applied to a bridge structure of pre-stressed concrete. A classical optimization strategy proposed by Matsumoto et al [110], which considers a priority among the objectives to be minimized, is applied to the structural design of motorcycles considering the torsional rigidity maximization, the reduction of the level of dynamic response, and the minimization of the weight of this structure. The proposed method is based on the lexicographic approach, and the optimization is performed successively from the superposition of single-objective optimizations (multiobjective fronts are not achieved).…”
Section: Classic Optimizationmentioning
confidence: 99%
“…A hierarchical approach is used by Matsumoto et al 91 in vehicle body design. They distinguish between "hard" and "soft" criteria.…”
Section: Surveymentioning
confidence: 99%
“…Clearly, such approach requires to decide which criteria to choose and which to drop. In (Matsumoto et al, 1993) and (Dym et al, 2002), it is shown how to develop a ranking among all criteria, and the related issue of decomposing a multiobjective design based on criteria influence is addressed in (Yoshimura et al, 2002(Yoshimura et al, , 2003. After these issues have been resolved, the reduced problem commonly takes the form shown in Figure 1.…”
Section: If a Design Is Pareto Optimal For A Subset Of All Performancmentioning
confidence: 99%